A new genus and new species of Myodochini from Australia (Hemiptera: Heteroptera: Rhyparochromidae) - Malipatil, M. B.; Gao, Cuiqing (Zootaxa, 2019)
Pseudolaryngodus spectabilis gen. et sp. nov., from Little Desert National Park in Victoria, Australia, is described and illustrated. The monotypic new genus superficially resembles the udeocorine genus Laryngodus Herrich-Schaeffer in general facies, and is sympatric with one of the species of Laryngodus. Pseudolaryngodus has some characters that share its tribal placement within both Udeocorini and Myodochini of the family Rhyparochromidae. However, it lacks inner laterotergites on abdomen, making it a Myodochini rather than a Udeocorini. Details of the relationships between these two genera, along with their tribal placements, are discussed.